Liquid Chromatography in Analysis of Bioactive Compounds for Pharmaceuticals, Cosmetics, and Functional Food Interest (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Plants produce a wide range of phytochemicals, known as non-nutrition compounds, to confirm their identity, and they are used for the production of natural pharmaceuticals, cosmetics, and functional food, among other things, due to their pro-health properties. The use of modern chromatographic techniques allows for accurate quantitative and qualitative identification of the above-mentioned phytochemicals and their natural products. Liquid chromatography is one of the most efficient and robust specific techniques due to the merits of convenience and strong separation ability, as well as a wide range of material applications for identification. Liquid chromatography is widely used to analyze plants, nutraceuticals, pharmaceuticals, and cosmetics and in natural product quality control or quantitative determination of bioactive compounds. The most commonly used for identifying different plant materials and pharmaceuticals are ultra- and high-performance liquid chromatography with UV-VIS, fluorescence, and diode array, which is equipped with mass spectrometry or tandem mass spectrometry detection methods. Therefore, for this Special Issue, we published studies concerning the latest scientific news, insights, and advances in the field of innovation of liquid chromatography for the analysis of bioactive compounds for pharmaceuticals, cosmetics, and functional food interests.